Periodontal ligament‐like tissue regeneration with drilled porous decalcified dentin matrix sheet composite. (28th September 2017) - Feng, G; Wu, Y; Yu, Y; Huang, L; An, S; Hu, B; Luo, J; Song, J
Abstract : Objective: In this study, we constructed a composite by combining the human dental follicle cell sheet and a manual drilled porous decalcified dentin matrix that was used to construct ectopic tissue‐engineered periodontal ligament‐like tissues in renal capsules of nude mice. Materials and methods: Human dental follicle cells were harvested from human lower third molars and then embedded into a temperature‐sensitive culture dish. These cells were then placed into frozen porous decalcified dentin matrix sheets and induced by 50 g/ml ascorbic acid. This established a "sandwich structure" in vitro implant that was placed in nude mice under the renal capsule. The mice were sacrificed at 4 and 8 weeks after implantation, and the implants were assessed after haematoxylin–eosin staining, Masson staining and immunohistochemical staining. Results: The experimental group showed a fibre structure between the dentin and HA‐TCP after 4 weeks. After 8 weeks, the collagen fibres increased, and the direction was perpendicular to the dentin. Immunohistochemistry showed positive staining in the osteopontin and periostin. Conclusion: The composite can induce ectopic bone and fibre formation, and the fibre had a certain directionality. Besides, the composite can maintain the stability of the periodontal ligament width.